Optimized Regulated Deficit Irrigation Management for Watermelon Cultivation in a Semiarid Region - Leite, Kelly Nascimento; Carvalho, Daniel Fonseca de; Martin- Benito, Jose Maria Tarjuelo; Sousa, Geocleber Gomes de; Padilla, Alfonso Dominguez (Journal of Agricultural Studies, 2021)
The present study aimed to validate the MOPECO crop simulation model and to determine a viable irrigation management for watermelon in the semiarid region of Northeast Brazil, using methodologies of optimized regulated deficit irrigation (ORDI) and constant deficit irrigation (CDI). The experiment was carried out during October to December 2013 and the second one from July to August 2014 in plots of land of producers in the Baixo Acaraú Irrigated Perimeter – Ceará, Brazil. Treatments were characterized by ORDI management (70, 80, 90% ETa/ETm ratio) and CDI management along the entire cycle (70, 80 and 90% ETm) and control treatment, irrigated with 100% of the water requirement of the crop (ETm). In terms of saving of water resources, the results showed that management with regulated deficit irrigation leads to favorable and economically viable results for the farmer, of water saving, especially in a situation of severe water scarcity, irrigation management with regulated water deficit (ORDI) can provide favorable and economically viable results for the farmer. The highest value of WUE (41.8 kg m-3) was obtained with the treatment of lowest water volume applied (352.1 L) in the second experiment, decreasing with the increase in the water volume used. The ORDI methodology represents a better water use efficiency for all treatments of deficit applied compared to CDI treatments. The difference of ORDI and CDI methodology provided an increase of up to 200% in the gross margin obtained with the exploration of the watermelon culture which represents a range of R 986.00 in profit in a situation of water scarcity, as in the case of the studied region, the strategy with water supply of 70% of ETa/ETm ratio regulated by phenological stage was recommended in order to obtain highest water use efficiency.